The rise of the BRICS in the global political economy : changing paradigms? - Lo, Vai Io; Hiscock, Mary; Edward Elgar Publishing (Cheltenham : Edward Elgar, 2014)
Taking an interdisciplinary approach, Vai Io Lo and Mary Hiscock, together with scholars and researchers from around the world, investigate the rise of the BRICS and assess the extent of their further development and influence from the perspectives of economics, international relations and law. Brazil, Russia, India, and China are expected to become the world's most influential economies, surpassing the current richest economies, by the middle of the 21st century. With the inclusion of South Africa in 2010, the BRICS span across four continents, creating an abundance of geopolitical clout, in addition to their potential economic dominance. This book examines the economic developments of individual BRICS countries, the current politico-economic condition of the BRICS vis-a-vis non-BRICS countries or groups, and the potential of the BRICS to bring about changing paradigms in the global political economy. This book is an essential resource for academics, researchers and students who are interested in the rise, development and impact of the BRICS economies. It will also be of interest to economists, political scientists, and specialists in international trade and investment.
1. The BRICS : an Indian perspective / H.E. Mr Biren Nanda -- 2. How solid are the BRICS? : an economic overview / Anthony J. Makin and Rashmi Umesh Arora -- 3. Fiscal policy and China's economic growth / Shuanglin Lin -- 4. Productivity differences, technology adoption and economic growth : the case of India / Radhika Lahiri and Shyama Ratnasiri -- 5. Brazil : a soft power rising with the BRICS towards a multipolar world / Raquel Dos Santos -- 6. Sino-Brazilian trade and antidumping concerns / Muruga Perumal Ramaswamy -- 7. Joining the BRICs : the case of South Africa / Laurence Boulle and Jessie Chella -- 8. Implications of the rise of the BRIC countries for Africa / Emmanuel T. Laryea -- 9. The BRICS : experiments with state capitalism and institutional investment / John Farrar and Mohamed Ariff -- 10. The power of the BRICS in the world trade and growth, analysing the macroeconomic impacts within and across the bloc / Ahmed Khalid -- 11. The BRICS+ : fault lines and opportunities / Umair Ghori -- 12. The BRICS : a model for living on the earth / Dilyara B. Karimova -- 13. The BRICS and Russia / Stephen Fortescue -- 14. New players, new rules? : the BRICS and global economic governance / Mark Thirlwell -- 15. BRICS and mortar(s) : breaking or building the global system? / Melissa Conley Tyler and Michael Thomas -- 16. China's path to development : does law matter? / Vai Io Lo -- 17. The role of the BRICS in international law in a multipolar world / Muthucumaraswamy Sornarajah -- 18. Conclusions : the BRICS -- ascendancy, decline or plateau? / Mary Hiscock and Vai Io Lo.
Includes bibliographical references and index.
Keywords: BRIC countries -- Economic conditions; BRIC countries -- Foreign relations; Developing countries -- Foreign relations; Developing countries -- Politics and government